ANALISIS KOMPARATIF YURIDIS KEBIJAKAN ANTIDUMPING ANTARA INDONESIA DAN FILIPINA - Novie Andriani Kesuma; Suhaidi Suhaidi; Mahmul Siregar; Jelly Leviza (USU LAW JOURNAL, 2014)
ABSTRACTDumping is the practice of selling commodities in foreign markets at less than normal value. The member countries of GATT / WTO have used instruments of antidumping duties against unfair trade practices and allows members to apply anti-dumping duties. Indonesia and Philippines are part of members in WTO and have ratified the GATT-WTO provisions and should have an obligation to obey all the set provisions to their national laws. Although in the application of anti-dumping provisions, Indonesia and the Philippines are still referring to the provisions in the Antidumping Agreement, but the application of laws regulations is different. The differences are to determine the normal value of antidumping policy in Indonesia does not regulate the export price calculations based on CIF or FOB. Other factors that may affect the normal value as exchange value of the currency, Antidumping policy in Indonesia also not set up a special relationship between a producer and an exporter that should be excluded in the determination of the domestic industry and about the protection of domestic industry in Indonesia is regulated Antidumping Policy on Custom Law, while in Antidumping policy in Philippines is set in its own provisions.Keywords : Antidumping, Comparative